2022
DOI: 10.3390/metabo12090841
|View full text |Cite
|
Sign up to set email alerts
|

LC-MS/MS Insight into Vitamin C Restoration to Metabolic Disorder Evoked by Amyloid β in Caenorhabditis elegans CL2006

Abstract: The transitional expression and aggregation of amyloid β (Aβ) are the most important causative factors leading to the deterioration of Alzheimer’s disease (AD), a commonly occurring metabolic disease among older people. Antioxidant agents such as vitamin C (Vc) have shown potential effects against AD and aging. We applied an liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) method and differential metabolites strategy to explore the metabolic disorders and Vc restoration in a human Aβ tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…According to the analysis of the co-citation count among the 10 references, most were human experiments, and four were randomized controlled trial (RCTs). The number of citations can be regarded as a relatively reasonable indicator to evaluate the quality of publications, which indicates that vitamins D, E, and B are the focus of current research, but recent research shows that vitamin C supplementation is a feasible strategy for prevention and treatment of AD (Hamid et al, 2022), Vitamin C treatment restored Aβ induced abnormal metabolites, and the role of antioxidants in the repair of AD metabolic disorder provide a new metabonomic observation and explanation (Zhang et al, 2022). Thus, VK2 may also play an important role in the prevention and treatment of AD (Popescu and German, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…According to the analysis of the co-citation count among the 10 references, most were human experiments, and four were randomized controlled trial (RCTs). The number of citations can be regarded as a relatively reasonable indicator to evaluate the quality of publications, which indicates that vitamins D, E, and B are the focus of current research, but recent research shows that vitamin C supplementation is a feasible strategy for prevention and treatment of AD (Hamid et al, 2022), Vitamin C treatment restored Aβ induced abnormal metabolites, and the role of antioxidants in the repair of AD metabolic disorder provide a new metabonomic observation and explanation (Zhang et al, 2022). Thus, VK2 may also play an important role in the prevention and treatment of AD (Popescu and German, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…LC-MS/MS analysis was conducted on all supernatants and QC samples, with the analysis parameters being set based on the methods we previously reported. 13…”
Section: Methodsmentioning
confidence: 99%
“…Synchronization of the worms was achieved using a previously described method. 13 The eggs were moved to NGM plates coated with OP50. After 48 h of incubation, L4 stage worms were collected for subsequent experiments.…”
Section: Maintenance and Synchronization Of C Elegansmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a metabolomic analysis of metabolites from the serum and brain tissue of β-amyloid (Aβ)-induced AD model mice revealed that Bifidobacterium breve treatment can restore Aβ-induced metabolomic disorder related to amino acids [ 22 ]. In our previous study, we used a metabolomic analysis to find that vitamin C can affect the tryptophan metabolism pathway in transgenic C. elegans [ 23 ].…”
Section: Introductionmentioning
confidence: 99%